Consensus Evidence-Based Clinical Practice Recommendations for the Diagnosis and Treat-To-Target Management of Osteoporosis in Chronic Kidney Disease Stages G4-G5D and Post-transplantation: An Initiative of Egyptian Academy of Bone Health - Yasser El Miedany; Naglaa Ali Gadallah; Eman Sarhan; Mathias Toth; Mona Mansour Hasab El Naby; Mohamed Elwy; Sahar Ganeb; Maha El Gaafary; Mohamed Mortada; Samah Ismail Nasef; Nevine Mohannad; Safaa Ali Mahran; et al. (Karger Publishers, 2022)
Objective: The aim of this study was to reach a consensus on an updated version of the recommendations for the diagnosis and Treat-to-Target management of osteoporosis that is effective and safe for individuals with chronic kidney disease (CKD) G4-G5D/kidney transplant. Methods: Delphi process was implemented (3 rounds) to establish a consensus on 10 clinical domains: (1) study targets, (2) risk factors, (3) diagnosis, (4) case stratification, (5) treatment targets, (6) investigations, (7) medical management, (8) monitoring, (9) management of special groups, (10) fracture liaison service. After each round, statements were retired, modified, or added in view of the experts' suggestions, and the percent agreement was calculated. Statements receiving rates of 7-9 by more than 75% of experts' votes were considered as achieving consensus. Results: The surveys were sent to an expert panel (n = 26), of whom 23 participated in the three rounds (2 were international experts and 21 were national). Most of the participants were rheumatologists (87%), followed by nephrologists (8.7%), and geriatric physicians (4.3%). Eighteen recommendations, categorized into 10 domains, were obtained. Agreement with the recommendations (rank 7-9) ranged from 80 to 100%. Consensus was reached on the wording of all 10 clinical domains identified by the scientific committee. An algorithm for the management of osteoporosis in CKD has been suggested. Conclusion: A panel of international and national experts established a consensus regarding the management of osteoporosis in CKD patients. The developed recommendations provide a comprehensive approach to assessing and managing osteoporosis for all healthcare professionals involved in its management.